Synthesis of Novel (9S)‐Acyloxy Derivatives of Quinidine and Dihydroquinidine as Insecticidal Agents. Issue 4 (30th March 2020) - Che, Zhiping; Yang, Jinming; Sun, Di; Tian, Yuee; Liu, Shengming; Lin, Xiaomin; Jiang, Jia; Chen, Genqiang
Abstract: Endeavor to discover biorational natural products‐based insecticides, two series (30) of novel (9 S )‐acyloxy derivatives of quinidine and dihydroquinidine were prepared and assessed for their insecticidal activity against Mythimna separata in vivo by the leaf‐dipping method at 1 mg/mL. Among all the compounds, especially four derivatives exhibited the best insecticidal activity with final mortality rates of 71.4 %, 75.0 %, 71.4 %, and 75.0 %, respectively. Relatively speaking, 9‐hydroxy group is well tolerated, and the results showed that after modification of the hydroxy group with an acyloxy group, the insecticidal activity was significantly increased; the configuration at C8/9 position is important for insecticidal activity, and the (9 S )‐configuration is optimal; modification of the out‐ring double bond is acceptable, and hydrogenation of the double bond enhances insecticidal activity. These preliminary results will pave the way for further modification of quinidine in the development of potential new insecticides. Abstract :